SMS-Phishing on Android Smart Phone - MAHMOD S. MAHMOD (College of Education for Pure Sciences, 2018)
Recently, mobile become the most significant device that used almost daily, and one of the most important service that offered by mobile operators is the SMS that used between mobiles, none of the mobile OS is contain a service that encrypt the send SMS where some needs to send an important, personal or secure message to the other mobile, and in this case mobiles OS needs an application to encrypt the SMS and then decrypted it on the other side. From this conception the idea of this research become to develop an application working on the devices that supports Android environment, this application encrypt the SMS before it sends from sender and then decrypt it by using the same application when it arrives to the recipient. The goal from Using the encryption Operation of the SMS is to convince that the user is using a secure SMS application that it sends an encrypted SMS where in fact that is not the truth, but the application find the loophole to take the encrypted SMS and sends the encrypted SMS to the third party (hacker) where the user will not noticed that the SMS went to the third party. Java language and an android developer tools like (ECLIPS) and other tools where used to build this application. This application is working on android environment and also needs a little space of memory and it works without leaves anything that refers to the third-party.